Synergies in VVER reactor long-term operation and aging: A comprehensive review of CAMIVVER, DELISA-LTO, and EVEREST projects - Hursin Mathieu; Perin Yann; Verrier Denis; Slugen Vladimir; Veternikova Jana Simeg (EPJ Nuclear Sciences & Technologies)
This paper reviews the synergies between three Euratom projects–CAMIVVER, DELISA-LTO, and EVEREST–focusing on the long-term operation (LTO) and safety assessment of VVER reactors. These projects address challenges associated with extending the lifespan of VVER reactors with implications to Europe's energy infrastructure. The CAMIVVER project concentrates on the development of VVER specific computational methods to support their safety assessments. Through the development of advanced simulation tools like APOLLO3® and CATHARE3, CAMIVVER aims to refine thermal-hydraulics and neutronics models for the VVER-1000 reactor type, supporting both existing reactor safety analyses and the qualification of alternative fuel sources. DELISA-LTO focuses on understanding and mitigating material degradation in VVER reactors, especially in the context of thermal aging and swelling. This project emphasizes non-destructive testing (NDT) and experimental validation to identify critical components and extend reactor lifespans safely. In parallel, EVEREST investigates advanced multi-physics approaches to improve the accuracy of reactor pressure vessel fluence assessments. By producing high-resolution experimental data, EVEREST seeks to validate these models for improved safety analysis of both VVER and other pressurized water reactors. A key synergy across these projects is the integration of experimental data and advanced modelling technics. Additionally, the projects share a focus on knowledge dissemination through workshops, training, and collaborative efforts, aimed at aligning regulatory, and industrial stakeholders with modelling and safety aspects associated with LTO of VVER. Together, CAMIVVER, DELISA-LTO, and EVEREST represent complementary approaches to addressing the aging and sustainability of VVER reactors, thereby contributing to Europe's energy security and decarbonization efforts.